(untitled) (African Journal of Biomedical Research, 2019)
Carboxymethyl cellulose (CMC) is generally believed to be biologically inert, non-toxic and non-allergic. Due to its bio-compatibility, bio-degradability and other rheological properties, it has found various uses in different aspects of human life, bio-medically and industrially; that includes, suspension of physiological extract (as a vehicle), drug delivery system, tissue regeneration, formation of smart materials, hydrogels, bone growth, surgical, ultrasound procedures and foodstuff formulations (thickening, binding), lubricant for drilling in oil industry and as a stabilizer and binder in cosmetic industry. In this study, we investigated the physiological effect of CMC on cognition and motor endurance. Wistar rats were orally administered with CMC, at 5mg/kg, 10mg/kg and 20mg/kg doses while a control group was given normal saline. Cognitive function was evaluated using novel object recognition task while motor endurance function was assessed using forepaw grip test. The results obtained showed that there was no significant difference (p > 0.05) in both working and long-term memory in all the groups when compared to the control. Although, not significant the group receiving 5mg/ml CMC showed a lower preference score (working memory) when compared to other groups. However, at the doses 5 mg/kg and 10 mg/kg, motor endurance was significantly improved. Findings in this study suggest that although CMC may not influence cognition in this study, it may not be completely physiologically inert since it influenced motor endurance which may not be undesirable, more studies should be carried out to ascertain its neurobehavioural activity, while caution is encouraged in its usage.